Biochemical repercussions of light spectra on nitrogen metabolism in spinach (Spinacia oleracea) under a controlled environment - Ramezani, Moazzameh; Thompson, Dalton; Moreno, Matte; Joshi, Vijay (Frontiers in Plant Science, 2023)
Introduction Selecting appropriate light spectra of light-emitting diodes (LEDs) and optimal nutrient composition fertilizers has become integral to commercial controlled environment agriculture (CEA) platforms. Methods This study explored the impact of three LED light regimes (BR: Blue17%, Green 4%, Red 63%, Far-Red 13% and infrared 3%, BGR; Blue 20%, Green 23%, Red 47%, Far-Red 8% and infrared 2%; and GR; Blue 25%, Green 41%, Red 32%, and Far-Red 2%) and nitrogen levels (3.6 and 14.3 mM N) on spinach (Spinacea oleracea). Results Under limited nitrogen (3.6 mM), BGR light increased the fresh shoot (32%) and root (39%) biomass than BR, suggesting additional green light’s impact on assimilating photosynthates under suboptimal nitrogen availability. Reduced chlorophyll (a and b) and carotenoid accumulation, electron transport rate (ETR), and higher oxalates under limited nitrogen availability highlighted the adverse effects of red light (BR) on spinach productivity. Increased activities of nitrogen-associated enzymes (GOGAT; Glutamate synthase, GDH; NADH-Glutamate dehydrogenase, NR; Nitrate reductase, and GS; Glutamine synthetase) in spinach plants under BGR light further validated the significance of green light in nitrogen assimilation. Amino acid distributions remained unchanged across the light spectra, although limited nitrogen availability significantly decreased the percent distribution of glutamine and aspartic acid. Conclusion Overall, this study demonstrated the favorable impacts of additional green light on spinach productivity, as demonstrated under BGR, than GR alone in response to nitrogen perturbation. However, the exact mechanisms underlying these impacts still need to be unveiled. Nevertheless, these outcomes provided new insights into our understanding of light spectra on spinach nitrogen metabolism.